A Comparative Analysis of Ethical Perceptions in Marketing Research: U.S.A. vs. Canada - Giacobbe, Ralph W.; Segal, Madhav N. (2000)
The study compares Canadian and U.S. marketing researchers' attitudes, perceptions and intentions related to several areas of ethical concern. A particular focus involves salience of norms common to marketing research codes of ethics (COEs) and familiarity of such codes to marketing research professionals. Researchers' attitudes towards today's ethical climate are identified and compared between the two countries. Relationships are examined between familiarity, ethical intention and salience. Results indicate that U.S. and Canadian marketing researchers have similar perceptions of the relative importance of specific ethical norms, but worldwide COEs do not reflect these perceptions. Canadian marketing researchers report having a greater familiarity with their firms' adopted COEs, but this finding is moderated by the type of researcher. Among other findings, results indicate that familiarity influences ethical intention only for highly salient issues.
Keywords: Ethical Concern; Market Research; Comparative Analysis; Marketing; Economic Growth